2019
DOI: 10.1177/0733464819883769
|View full text |Cite|
|
Sign up to set email alerts
|

Can a Green Care Informal Learning Program Foster Active Aging in Older Adults? Results From a Qualitative Pilot Study in Central Italy

Abstract: Due to population aging worldwide, it is important for Health Care Systems to design new services fostering Active Aging dimensions (e.g., physical health, psychological well-being, social engagement, and lifelong learning). The aim of this pilot study was to develop new services fostering Active Aging dimensions by means of a 12-month green care informal learning program targeting 112 individuals among community-dwelling older people and day care center users. The impact of the intervention was assessed throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 40 publications
(44 reference statements)
0
8
0
1
Order By: Relevance
“…22 Similar to this one, other studies also found associations between deschooled or informal learning and behaviors. 23,24,25,26 Therefore, during the pandemic situation, day-to-day human mobility and interpersonal risky contact can be shrunk by increasing the learning about COVID-19 among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…22 Similar to this one, other studies also found associations between deschooled or informal learning and behaviors. 23,24,25,26 Therefore, during the pandemic situation, day-to-day human mobility and interpersonal risky contact can be shrunk by increasing the learning about COVID-19 among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…These EE programs used to include a combination of social contact, multisensory stimulation, games, hikes, gymnastics lessons, going up and down stairs, music and arts (Aronoff et al., 2016; Raine et al., 2003; Woo & Leon, 2013; Woo et al., 2015). These interventions have been successfully incorporated as an adjuvant treatment for antisocial behaviour, schizophrenia, autism spectrum and attention deficit/hyperactivity disorders (Ball et al., 2019; Raine et al., 2003) and also reduce age‐related cognitive decline and increase well‐being both in healthy and unhealthy individuals (de Vries et al., 2003; Queen et al., 2020; Santini et al., 2020). Exercise and physical activity are two fundamental components of EE (Queen et al., 2020; Simpson & Kelly, 2011) capable of potentiating brain functions in healthy and unhealthy humans (Fernandes et al., 2017; Stillman et al., 2020).…”
Section: The Immersion In Green Environments As a Strategy For Stress...mentioning
confidence: 99%
“…It is important to iterate that the therapeutic benefits of factors useful in creating optimal healing environments are not limited to healthcare settings or even in unhealthy individuals. More recent work has explored the use of nature-based stimuli as a therapeutic driver for well-being in healthy aged individuals Santini et al, 2019). Horticultural therapy within community or home gardens and the inclusion of green spaces within neighborhoods, hospitals, and nursing homes shows incredible promise to benefit people across a wide spectrum of health.…”
Section: Optimization Of Environment In Medicinementioning
confidence: 99%